2013
DOI: 10.1021/bm400125w
|View full text |Cite
|
Sign up to set email alerts
|

Nephila clavipes Flagelliform Silk-Like GGX Motifs Contribute to Extensibility and Spacer Motifs Contribute to Strength in Synthetic Spider Silk Fibers

Abstract: Flagelliform spider silk is the most extensible silk fiber produced by orb weaver spiders, though not as strong as the dragline silk of the spider. The motifs found in the core of the Nephila clavipes flagelliform Flag protein are: GGX, spacer, and GPGGX. Flag does not contain the polyalanine motif known to provide the strength of dragline silk. To investigate the source of flagelliform fiber strength, four recombinant proteins were produced containing variations of the three core motifs of the Nephila clavipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 72 publications
5
97
0
Order By: Relevance
“…In total, >32 million features are annotated on the N. clavipes draft genome (Supplementary Table 8), which was achieved using (i) our transcriptome from all isolates, (ii) results from two gene prediction algorithms, (iii) libraries of transposable elements and repeated motifs, and (iv) coding sequences from related species 18,19 (Supplementary Table 8). Using gene modeling, we conservatively predict 14,025 genes present in the N. clavipes genome; 2,023 gene models transcribe >1 alternative spliceoform, resulting in 3,937 additional transcripts for a total of 17,962 mRNAs in the final gene set (Supplementary Table 9).…”
Section: An Annotated Genome For N Clavipesmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, >32 million features are annotated on the N. clavipes draft genome (Supplementary Table 8), which was achieved using (i) our transcriptome from all isolates, (ii) results from two gene prediction algorithms, (iii) libraries of transposable elements and repeated motifs, and (iv) coding sequences from related species 18,19 (Supplementary Table 8). Using gene modeling, we conservatively predict 14,025 genes present in the N. clavipes genome; 2,023 gene models transcribe >1 alternative spliceoform, resulting in 3,937 additional transcripts for a total of 17,962 mRNAs in the final gene set (Supplementary Table 9).…”
Section: An Annotated Genome For N Clavipesmentioning
confidence: 99%
“…The silk classes of a typical 'gluey silk' orb-weaver (Araneoidea) female include (i) major ampullate silk, which exhibits great tensile strength and is employed in draglines, bridgelines, and web radii 11,12 ; (ii) minor ampullate silk, used for inelastic temporary spirals during web building 11,12 ; (iii) cement-like piriform silk that bonds fibers together and to other substrates 13,14 ; (iv) strong, yet flexible aciniform silk used for prey wrapping and egg case insulation 15 ; (v) tubuliform and cylindriform silk that constitutes the tough outer layer of egg cases 16,17 ; (vi) flagelliform silk that exhibits unparalleled extensibility and is used in the capture spiral 18,19 ; and (vii) the viscous and sticky aggregate silk that aids in prey capture [20][21][22][23][24] . Many spider species produce just a subset of these silk classes, and some produce yet other silk types, including cribellate silk 25 .…”
mentioning
confidence: 99%
“…Wet-spinning requires a viscous solution 9,42 ; however, there is a fine balance between sufficient viscosity and an overly viscous state that cannot be extruded through the spinner. After trial and error, it was found that 5% w/v W 3 being insufficiently viscous and 10% w/v W 3 being sufficiently viscous to allow for wet-spinning but difficult to routinely prepare and employ, an optimum dope composition of 8% w/v W 3 in 70% HFIP/30% H 2 O was established.…”
Section: Production and Characterization Of W 3 Protein Dopementioning
confidence: 99%
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ).…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
“…Dragline silk, one of the strongest types of silk, is produced in the major ampullate gland and is used as the web frame and lifeline for the spider (5). The proteins that form the core of dragline silk are termed major ampullate spidroins (MaSp), 2 and they have three main domains: a long, flexible, highly repetitive central domain known as the repeat region flanked by smaller, globular, non-repetitive N-terminal and C-terminal domains (NTD and CTD, respectively) (6 -8).…”
mentioning
confidence: 99%